Reliability of the Tuck Jump Assessment Using Standardized Rater Training - Kevin Racine; Meghan Warren; Craig Smith; Monica R. Lininger (International Journal of Sports Physical Therapy)
# BACKGROUND The Tuck Jump Assessment (TJA) is a test used to assess technique flaws during a 10-second, high intensity, jumping bout. Although the TJA has broad clinical applicability, there is no standardized training to maximize the TJA measurement properties.